2001
DOI: 10.1002/1520-6300(200101/02)13:1<57::aid-ajhb1007>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Blood group, red cell, and serum protein variation in the Cabecar and Huetar, two Chibchan Amerindian tribes of Costa Rica

Abstract: Genetic variation, using blood groups and red cell and serum proteins, was surveyed in the Cabecar of Chirripo and the Huetar of Quitirrisi, Costa Rica. Thirty-nine loci were screened in a sample of 91 Cabecars and 40 loci in 45 Huetars. Twenty-seven loci were monomorphic in the Cabecar and 30 in the Huetar. The proportions of polymorphic loci (P), out of 34 studied by electrophoresis, were 0.235 and 0.177, respectively. Estimated gene diversities (H) of the polymorphic loci were 0.050 in the Cabecar and 0.053… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The observed low frequency of the decreased-activity allele CYP2C9*2 in the most Amerindian populations from Costa Rica (Bribri, Cabécar, Maleku and Guaymí) (Azofeifa, Ruiz, & Barrantes, 2001), is consistent with other studies on North-and South-Amerindians, which reported frequencies from 0 to 4.8 % for this allele (Céspedes-Garro et al, 2015). Noteworthy, the high CYP2C9*2 frequency in the Huetar (8.3 %) is similar to that of the Costa Rican admixed population (7.7 %), in agreement with reports that estimate that the Huetar groups have European and African admixture as high as 3.9 to 32.9 % (Barrantes, 1993;Santos, Ward, & Barrantes, 1994;Bieber, Bieber, Rodewald, & Barrantes, 1996;Azofeifa et al, 2001;Ruiz-Narváez et al, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…The observed low frequency of the decreased-activity allele CYP2C9*2 in the most Amerindian populations from Costa Rica (Bribri, Cabécar, Maleku and Guaymí) (Azofeifa, Ruiz, & Barrantes, 2001), is consistent with other studies on North-and South-Amerindians, which reported frequencies from 0 to 4.8 % for this allele (Céspedes-Garro et al, 2015). Noteworthy, the high CYP2C9*2 frequency in the Huetar (8.3 %) is similar to that of the Costa Rican admixed population (7.7 %), in agreement with reports that estimate that the Huetar groups have European and African admixture as high as 3.9 to 32.9 % (Barrantes, 1993;Santos, Ward, & Barrantes, 1994;Bieber, Bieber, Rodewald, & Barrantes, 1996;Azofeifa et al, 2001;Ruiz-Narváez et al, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…Central and South Amerindians showed no significant differences. But in Central America only the two most common haplotypes (HP5 and HP1) were found, and this low genetic variability may have occurred because of isolation followed by a population reduction (Barrantes et al 1990; Azofeifa et al 2001). The difference observed among populations within groups (∼15%) was probably due to genetic structure within South America.…”
Section: Discussionmentioning
confidence: 99%